BCL-2 inhibitors in hematological malignancies: biomarkers that predict response and management strategies - Markouli, Mariam; Pagoni, Maria N.; Diamantopoulos, Panagiotis (Frontiers in Oncology, 2025)
Apoptosis is an essential characteristic of cancer and its dysregular promotes tumor growth, clonal evolution, and treatment resistance. B-cell lymphoma-2 (BCL-2) protein family members are key to the intrinsic, mitochondrial apoptotic pathway. The inhibition of the BCL-2 family pro-survival proteins, which are frequently overexpressed in B-cell malignancies and pose a fundamental carcinogenic mechanism has been proposed as a promising therapeutic option, with venetoclax (ABT-199) being the first FDA-approved BCL-2 inhibitor. Unfortunately, although BCL-2 inhibition has shown remarkable results in a range of B-cell lymphoid cancers as well as acute myeloid leukemia (AML), the development of resistance significantly reduces response rates in specific tumor subtypes. In this article, we explain the role of BCL-2 family proteins in apoptosis and their mechanism of action that justifies their inhibition as a potential treatment target in B-cell malignancies, including chronic lymphocytic leukemia, multiple myeloma, B-cell lymphomas, but also AML. We further analyze the tumor characteristics that result in the development of intrinsic or inherited resistance to BCL-2 inhibitors. Finally, we focus on the biomarkers that can be used to predict responses to treatment in the name of personalized medicine, with the goal of exploring alternative strategies to overcome resistance.